Epidemiological analysis of hysterectomies performed at the public health system in the largest Brazilian city - Augusto,Carolina Fornaciari (2021)
SUMMARY OBJECTIVE: To analyze the public data of hysterectomies performed in the only health system in the city of São Paulo between 2008 and 2018. METHODS: The following public health system data were extracted and analyzed: age, technique, number of surgeries, mortality during hospitalization, length of stay in the establishment (days), and amounts paid by the public network. RESULTS: A total of 20,119 procedures were analyzed. The most prevalent procedure was total hysterectomy (43.2%), followed by vaginal hysterectomy (26.7%), subtotal hysterectomy (24.3%), and laparoscopic hysterectomy (5.8%). Early discharge (hospital stay of up to 1 day) was more prevalent in cases of vaginal hysterectomy (39%). We observed a marked downward trend in the number of total hysterectomies. Total hysterectomy was the most expensive procedure; no significant difference was noted in the cost of vaginal versus laparoscopic hysterectomy. We noticed a trend of rising costs over the years. The most frequent hospital admission code was that of leiomyoma of the uterus in cases of total, subtotal, and laparoscopic hysterectomy. CONCLUSION: Despite the decrease in the number of hysterectomies over the 11-year study period in São Paulo, it remains in high demand mainly for the treatment of uterine leiomyomatosis. Laparoscopic hysterectomy has been gaining ground and showed a slightly upward trend with a shorter hospital stay. Laparoscopic and vaginal hysterectomy required less financial support from the health system than open surgery.